Metabolomic profile and Bioassay-guided Phytochemical analysis of the Stems from Cissus trifoliata, evaluation of their Antibacterial and Cytotoxic activity, and determination of the Mechanism of Action of one active compound - Méndez López, Luis Fernando (2020)
Objectives and methods: Bioprospecting the metabolic profile of medicinal plants has provided a reliable resource for drug discovery and advancements in biomedical research. Cissus trifoliata (L.) L belongs to the Vitaceae family and is an important medicinal plant used in Mexico for the management of infectious diseases and tumors. The present study aimed to identify the metabolic profile of the extracts from the stems of C. trifoliata and evaluate their antibacterial and cytotoxic activities. Additionally, to identify the molecules that contribute to their biological activity and to explore the mechanism of action of one active compound. The hexane, CHCl3-MeOH, and aqueous extracts were prepared from the stems of C. trifoliata and their metabolic profile was investigated by column chromatography, NMR, GC-MS, and LC-MS. The antibacterial activity was determined by the broth microdilution method and the cytotoxicity against cancer cell lines using the MTS proliferation assay. A bioassay-guided study of the CHCl3-MeOH extract was performed using WST-1 to identify the active constituents responsible for the antiproliferative effects against cancer cells. Additionally, microarrays were used to identify the mechanism of action of one active compound against prostate cancer cells.